Etiological, sociodemographic and clinical characteristics of sexually transmitted infections and M. genitalium resistance in Shenzhen: a multicenter cross-sectional study in China - Wang, Feng; Zhang, Chi; Xiu, Leshan; Li, Yamei; Zeng, Yaling; Li, Yizhun; Cai, Yumao; Peng, Junping (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionThis study aims to determine the etiological, sociodemographic, and clinical characteristics of STIs, and the level of resistance in M. genitalium in Shenzhen, a representative first-tier city of southern China.MethodsA multicenter cross-sectional study was conducted and 7886 sexually active participants attending STI-related departments were involved from 22 hospitals. Nine STI-related organisms including N. gonorrhoeae, C. trachomatis, T. vaginalis, M. genitalium, HSV-1, HSV-2, M. hominis, U. parvum, and U. urealyticum were screened.ResultsBeing single or divorced was associated with increased detection of N. gonorrhoeae, C. trachomatis, M. genitalium, HSV-1, HSV-2 and M. hominis. Lower education level was associated with increased detection of C. trachomatis, HSV-2 and M. hominis. No insurance coverage was an independent risk factor for T. vaginalis, M. hominis and U. parvum positivity. Three resistance-determining regions related to macrolide and fluoroquinolone were sequenced in 154 M. genitalium positive samples, among which 90.3% harbored mutations related to macrolide or fluroquinolone resistance and 67.5% were multidrug-resistant M. genitalium. A2072G in 23S rRNA and Ser83Ile in parC were the most common mutations. M. hominis was associated with manifestations of bacterial vaginosis in female and epididymitis in male.ConclusionsSingle or divorced individuals, those with lower education level and individuals without insurance are higher-risk key populations for STIs. The prevalence of antimicrobial-resistant M. genitalium in Shenzhen is high. Detection of M. hominis increased significantly with lower education level and no health insurance coverage, and it is associated with bacterial vaginosis or epididymitis, indicating that M. hominis deserves further attention.